EFFECT OF A WORKBOOK IN HEALTH EDUCATION ON SELF-EFFICACY AND QUALITY OF LIFE OF PATIENTS WITH CORONARY HEART DISEASE - Aan Nuraeni; Ristina Mirwanti; Anastasia Anna (Belitung Raya Foundation, Indonesia, 2019)
Background: Coronary Heart Disease (CHD) has a high recurrence in Indonesia. This condition may occur as a result of the failure of compliance with post-acute management following a heart attack by CHD patients. One of the causes is the lack of effective health education. Objective: The aim of this study was to identify the feasibility of the workbook in improving patients’ self-efficacy (SE) and quality of life (QoL). Methods: This research used a quasi-experimental with pretest-posttest control design. A pretest was done to the patients who were treated in the cardiac intensive unit, and a posttest was carried out at the end of the first and second month after the pretest. The population was all post-acute CHD patients who were admitted to the cardiac intensive unit in one of the referral hospitals in West Java, Indonesia. A purposive sampling was used and obtained 39 respondents who were divided into control and intervention groups. The intervention group was given a health education using a workbook, and the control group was given a direct health education. Self-efficacy was measured using a questionnaire developed by the authors, with high validity and reliability. A SF-12 instrument was used for measuring the quality of life. Data were analyzed using a descriptive quantitative analysis such as mean, Mann Whitney test, and Independent t-test. To estimate the effects of the intervention to QoL and SE, Kruskal Wallis test and One-way ANOVA were used. Results: The results showed that there was an increase in SE and QoL in both groups, either in the posttest 1 or posttest 2. The comparison of QoL in the pretest, posttest I and II obtained p=.452, .741, and .826, while SE between and within groups obtained p = .732, .220, and .009, respectively. Conclusions: Health education using the workbook was significantly more effective to increase SE than QoL of the CHD patients.